Analisis Pengaruh Word of Mouth dan Marketing Mix terhadap Keputusan Pembelian Konsumen Ribur Korean Cuisine - Panggabean, Erika Christine; Manullang, Endang Juliati (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of word of mouth and marketing mix on purchasing decisions at Ribur Korean Cuisine. The object of this research is consumers of Ribur Korean Cuisine. This type of research is quantitative research. The data collection method used in this research is by distributing questionnaires via google form. The population of this study amounted to 150 people. The sampling technique used the Slovin formula, where the number of samples obtained was 60 people. The results showed that the t test results for the word of mouth variable (X1) were 0.993 < 1.67203 with a significance level of 0.325> 0.05, which means that word of mouth has no significant effect on consumer purchasing decisions (Y). Meanwhile, the t test results for the marketing mix variable of 3.173> 1.67203 with a significance level of 0.002 <0.05 indicate that the marketing mix has a significant effect on consumer purchasing decisions. And for the results of the F test of 10.203> 2.40 and a significance of 0.000 <0.05, which shows that word of mouth and marketing mix together have a significant influence on purchasing decision variables